Photocoagulation of choroidal neovascular membranes with a diode laser. - Ulbig, M W (1993)
Nine eyes with parafoveal choroidal neovascular membranes due to age-related macular degeneration or angioid streaks were treated with a diode laser and were followed up to 40 weeks (mean 26 weeks). Angiographically proved closure of the membrane was achieved in seven eyes. Four lesions needed a second treatment for growth of subretinal neovascular tissue. Post-treatment visual acuity ranged from 6/9 to 6/60. Two eyes developed subfoveal membranes resulting in poor visual acuity. The morphology of the diode laser lesions differed from that of the argon green laser and was more similar to that of the krypton laser, producing a 'black hole' on the fluorescein positive print. In one particular eye fluorescein angiography revealed subfoveal choroidal non-perfusion next to the site of the diode lesion suggesting choroidal vascular closure.